Development of techniques for characterisation of scintillation materials for cryogenic application - Mikhailik, V; Kraus, H (2013)
The multi-photon counting (MPC) technique was designed to record photon emission of scintillators and, as a very powerful method of material characterisation, is enjoying increasing popularity. The technique is especially advantageous for the analysis of slow scintillation processes and the investigation of temperature-dependent scintillator properties. The paper describes the latest development of the technique aiming to improve performance and widen the scope of applications. The results from characterising MgF 2 are presented to illustrate the capabilities of the MPC technique. © 2012 Elsevier Ltd. All rights reserved.